Desarrollo de un regulador de carga para sistemas fotovoltaicos aplicando instrumentación virtual - Patino Abella, Johan Sebastian; Tello Reyes, Juan Sebastian; Hernandez Mora, Johann Alexander (Ingeniería, 2008)
In this work, the procedure used to develop a virtual load regulator for autonomous photovoltaic systems is described. The regulator includes data acquisition and control, real time measuring of batteries voltage, and event tracking that records data items such as hour,day, month, year, kind of event and voltage magnitude in an Excel ® file. This load regulator was implemented applying virtual instrumentation through the LabVIEW® graphic programming software and a highspeed sampling rate and USB-enabled data acquisition device by National Instruments(c). Tests indicate that the virtual load regulator operation on a autonomous photovoltaic system meets the operating parameters established for these kind of devices, achieving optimal information processing, as well as having advantages and innovations compared to conventional charge controllers.